2010
DOI: 10.1016/j.chembiol.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Pore Drug Binding Site of Microtubules with Fluorescent Taxanes: Evidence of Two Binding Poses

Abstract: The pore site in microtubules has been studied with the use of Hexaflutax, a fluorescent probe derived from paclitaxel. The compound is active in cells with similar effects to paclitaxel, indicating that the pore may be a target to microtubule stabilizing agents. While other taxanes bind microtubules in a monophasic way, thus indicating a single type of sites, Hexaflutax association is biphasic. Analysis of the phases indicates that two different binding sites are detected, reflecting two different modes of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 33 publications
6
32
0
Order By: Relevance
“…Zampanolide strongly inhibited paclitaxel binding without interfering with peloruside A binding, and its specific binding to the taxane luminal site can impede or modify the taxane pore site. Thus hexaflutax (a fluorescent taxane probe that binds to the taxane pore site 34 ) did not bind to tubulin in the presence of zampanolide even at stoichiometric concentrations with tubulin. 23 The apparent binding constants of both 1 and 3 increased with temperature, indicating possible covalent binding to microtubules, 35,36 similar to that of cyclostreptin.…”
Section: Mechanism Of Actionmentioning
confidence: 96%
“…Zampanolide strongly inhibited paclitaxel binding without interfering with peloruside A binding, and its specific binding to the taxane luminal site can impede or modify the taxane pore site. Thus hexaflutax (a fluorescent taxane probe that binds to the taxane pore site 34 ) did not bind to tubulin in the presence of zampanolide even at stoichiometric concentrations with tubulin. 23 The apparent binding constants of both 1 and 3 increased with temperature, indicating possible covalent binding to microtubules, 35,36 similar to that of cyclostreptin.…”
Section: Mechanism Of Actionmentioning
confidence: 96%
“…The kinetic techniques used to measure the interaction of hexaflutax with the pore site revealed it does so in two distinct ways, likely due to different rearrangements of taxane and fluorescein binding; one in which interactions are made only with β -tubulin subunits and another in which the interactions are made with both α and β -tubulin subunits. 123 This work showed that both binding interactions proposed separately by Freedman and Magnani are indeed possible. Hexaflutax led to the characteristic microtubule bundling and mitotic arrest seen with other microtubule stabilizers, albeit with much lower potency than cyclostreptin, suggesting that binding at the pore site may be sufficient for microtubule stabilization.…”
Section: Binding Sites and Molecular Effects Of Microtubule Stabilimentioning
confidence: 66%
“…however, proposed that the taxane core is only bound to a single β -tubulin subunit with the side chain bound to α-tubulin. 137 Diaz aimed to better characterize the interactions of taxane-site binding agents within the pore site 123 using hexaflutax, a fluorescent taxane derivative that binds to the external pore site on microtubules with no observable modification of the interior luminal site. The kinetic techniques used to measure the interaction of hexaflutax with the pore site revealed it does so in two distinct ways, likely due to different rearrangements of taxane and fluorescein binding; one in which interactions are made only with β -tubulin subunits and another in which the interactions are made with both α and β -tubulin subunits.…”
Section: Binding Sites and Molecular Effects Of Microtubule Stabilimentioning
confidence: 99%
See 1 more Smart Citation
“…These probes exhibited potent tubulin assembly promotion and tumor cell killing activities, thus have been proven to be useful as tools for the determination of thermodynamic parameters and exploration of ligand–microtubule interactions. 66, 67 …”
Section: Microtubules and Taxoid Anticancer Agentsmentioning
confidence: 99%